Predicting Buildings' Energy Use: Is the Occupant-Centric “Performance Gap” Research Program Ill-Advised? - Mahdavi, Ardeshir; Berger, Christiane (Frontiers in Energy Research, 2019)
The term "performance prediction" commonly denotes the analysis of building designs, for instance, in view of their future energy demand. The notion of "performance gap" is invoked, when actual performance of buildings does not match preceding predictions. There has been a recent trend to attribute the so-called energy performance gap predominantly (sometimes even entirely) to user behavior. As a consequence, a number of research efforts (subsumed hear as "the performance gap research program") pursue more accurate predictions of user behavior and the exploitation of user-related energy efficiency potential via behavioral modification. In the present contribution, we critically revisit the premises and orientation of these efforts. Firstly, we suggest to situate the related discourse within a structured conceptual framework to objectively discuss the spectrum of potential contributors to the errors in building energy use predictions. Secondly, we examine the frequently purported utility of probabilistic methods and uncertainty analysis as an effectual remedy to the problem of performance gap.